2018
DOI: 10.1016/j.scr.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing proliferation and optimizing the culture condition for human bone marrow stromal cells using hypoxia and fibroblast growth factor-2

Abstract: This study aimed to determine the cellular characteristics and behaviors of human bone marrow stromal cells (hBMSCs) expanded in media in a hypoxic or normoxic condition and with or without fibroblast growth factor-2 (FGF-2) treatment. hBMSCs isolated from the vertebral body and expanded in these four groups were evaluated for cellular proliferation/migration, colony-forming units, cell-surface characterization, in vitro differentiation, in vivo transplantation, and gene expression. Culturing hBMSCs using a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
3
18
1
1
Order By: Relevance
“…It has been well-established that physioxic conditions enhance the anabolic response in MSC chondrogenesis [15,37,39,40,41,42,43,51,52]. Anderson et al (2016) showed that the reaction under physioxia is related to the GAG production under hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-established that physioxic conditions enhance the anabolic response in MSC chondrogenesis [15,37,39,40,41,42,43,51,52]. Anderson et al (2016) showed that the reaction under physioxia is related to the GAG production under hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…With this as a caveat, the majority of studies of MSC chondrogenesis either in pellet or scaffold cultures indicates an increase in chondrogenic genes ( COL2A1 and ACAN ) and matrix formation under physioxia [33,41,42,43,47,49,50,52,55,62,71,72,76,77,78,79,82,86,87,88,90,92,93,95,97]. Furthermore, it has also been shown that physioxia is a more potent promoter of chondrogenesis than dynamic (compressive) loading with no synergistic effect upon combining the parameters [78,98].…”
Section: Physioxia and Msc Chondrogenesismentioning
confidence: 99%
“…MSC that have been pre-expanded or preconditioned under physioxia prior to subsequent chondrogenesis under the same conditions demonstrated an enhancement in matrix deposition and a reduction in collagen X and other hypertrophy markers compared with non-preconditioned chondrogenic MSCs differentiated under physioxia (summarised in Table 2) [41,42,43,45,46,48,49,52,62,89,90,91,93,94,95,97]. Martin-Rendon et al (2007) showed that preconditioned MSCs had higher SOX9 gene expression and subsequent pellet wet weight [89].…”
Section: Physioxia and Msc Chondrogenesismentioning
confidence: 99%
“…Combined delivery of FGF-2, transforming growth factor-β1, and adipose-derived stem cells from an engineered periosteum to a critical-sized mouse femur defect yielded improved bone allograft healing (23). The concurrent application of hypoxia and FGF-2 could provide a favorable condition for culturing human bone marrow-derived stem cells to be used in clinical applications associated with bone tissue engineering, due to the enhancement of cellular proliferation and regenerative potential (24). The effects of temporal manipulation were achieved by applying FGF-2 and transforming growth factor-β3 on the derivation of proliferative chondrocytes from mesenchymal stem cells (25).…”
Section: Discussionmentioning
confidence: 99%